Efficacy and Safety of Intravenous Acetaminophen for Pain Control after Surgery in Adults: A Meta-Analysis - Putra, Ade Cahyana (Open Access Indonesian Journal of Medical Reviews, 2024)
Intravenous (IV) acetaminophen is increasingly used in multimodal postoperative pain management. This meta-analysis aims to assess the efficacy and safety of IV acetaminophen compared to placebo or other analgesics in adult surgical patients. A systematic search of PubMed, Embase, and Cochrane Library databases was conducted from January 2018 to December 2023. Randomized controlled trials (RCTs) evaluating IV acetaminophen for postoperative pain in adults were included. Primary outcomes were pain intensity and opioid consumption. Secondary outcomes included adverse events and length of hospital stay. Twenty-three RCTs (n=4,128) were included. IV acetaminophen significantly reduced postoperative pain scores compared to placebo (standardized mean difference [SMD] -0.32; 95% CI -0.41 to -0.23) and opioid consumption (SMD -0.28; 95% CI -0.37 to -0.19). No significant difference was found in pain reduction between IV acetaminophen and other analgesics. IV acetaminophen was associated with a lower incidence of nausea and vomiting compared to opioids. IV acetaminophen is an effective and safe analgesic for postoperative pain management in adults, reducing pain intensity and opioid consumption. It may also have a favorable adverse event profile compared to opioids.